2022
DOI: 10.1177/17585732221081012
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Benign Prostatic Hyperplasia on Postoperative Complications and Periprosthetic Joint Infections Following Total Shoulder Arthroplasty

Abstract: Background A recently proposed risk factor for periprosthetic joint infections (PJI) in men is benign prostatic hyperplasia (BPH). The objective was to explore the association of BPH on 1) 90-day complications, 2) length of stay (LOS), 3) readmission rates, and 4) healthcare expenditures following total shoulder arthroplasty (TSA). Methods A retrospective query was performed using a nationwide claims database from January 2005 to March 2014 for male patients undergoing primary TSA. The study cohort included 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recent studies have investigated benign prostatic hyperplasia (BPH), particularly symptomatic BPH (sBPH), as a potential risk factor for periprosthetic joint infection (PJI) in total joint arthroplasty [6][7][8]21]. Two studies found sBPH to be associated with a higher risk of PJI 90 days after total shoulder arthroplasty [7] and at least 1 year after primary or revision THA and TKA [21]. Other studies found no association between sBPH and PJI within 2 years after reverse shoulder arthroplasty [6] and primary THA and TKA [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated benign prostatic hyperplasia (BPH), particularly symptomatic BPH (sBPH), as a potential risk factor for periprosthetic joint infection (PJI) in total joint arthroplasty [6][7][8]21]. Two studies found sBPH to be associated with a higher risk of PJI 90 days after total shoulder arthroplasty [7] and at least 1 year after primary or revision THA and TKA [21]. Other studies found no association between sBPH and PJI within 2 years after reverse shoulder arthroplasty [6] and primary THA and TKA [8].…”
Section: Introductionmentioning
confidence: 99%
“…With the limited and conflicting evidence regarding the association between sBPH and PJI [6][7][8]21], there is no consensus about how important sBPH is among patients undergoing THA, and further investigation of this topic is warranted. As only two studies have compared the rate of PJI among THA patients with and without a history of sBPH [8,21]-one study was a single-institution study including revision procedures [21] and the other had a sample size of only 1745 primary THA patients [8]-we hoped to use a more robust sample size with a national database to settle the controversy on the association between sBPH and PJI after primary THA.…”
Section: Introductionmentioning
confidence: 99%